2021
DOI: 10.1017/s1368980021001750
|View full text |Cite
|
Sign up to set email alerts
|

Profiling household double and triple burden of malnutrition in sub-Saharan Africa: prevalence and influencing household factors

Abstract: Objective: Undernutrition and anaemia (the commonest micronutrient deficiency), continue to remain prevalent and persistent in sub-Saharan Africa (SSA) alongside a rising prevalence of overweight and obesity. However, there has been little research on the co-existence of all three conditions in the same household in recent years. The current study examines the co-existence and correlates of the different conditions of household burden of malnutrition in the same household across SSA. Setting:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 48 publications
5
36
1
Order By: Relevance
“…Children who grew up with relatively older household heads were less likely to be anaemic compared to children with younger heads of household. Previous studies found similar results [ 36 38 ]. The possible explanation for this is that older heads have experience with childcare and are likely to take better care of children to prevent illness than younger household heads [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Children who grew up with relatively older household heads were less likely to be anaemic compared to children with younger heads of household. Previous studies found similar results [ 36 38 ]. The possible explanation for this is that older heads have experience with childcare and are likely to take better care of children to prevent illness than younger household heads [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Sassi et al (2018) estimated the magnitude of mothers with overweight and children with anaemia living in Tunisia to be 24.4%, which is similar to our pooled prevalence for households with overweight/obesity among mothers and anaemia among children for the Eastern Mediterranean region (24.1%). Christian and Dake (2021) examined the household‐level double and triple burden of malnutrition in Sub‐Saharan African countries. Our study used different definitions of intra‐household DBM, and therefore, our estimates are not directly comparable.…”
Section: Discussionmentioning
confidence: 99%
“…A review from 2014 also demonstrated how the increase in sugar intake, with an intake higher than the recommended 40 g per day, was a powerful predictor of overweight and obesity in countries of Sub-Saharan Africa, including Tanzania [ 55 , 56 ]. A recent study, conducting data between 2008 and 2017, from 23 countries of Sub-Saharan Africa including Tanzania and Mozambique found out that a triple burden of malnutrition (anemia, underweight and overweight) was present in 5–8% of the households and that interventions must address overweight/obesity but also undernutrition and anemia [ 57 ]. A study on 976 adolescents from Ghana stated an even higher prevalence of overweight than in the present study with almost half of female and male adolescents (48%) overweight, while approximately one-third of males (30.5%) and half of females (52.2%) had mild (females:110–119 g/L, males: 110–129 g/L) to severe (<80 g/L) anemia [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%